تقييم واقع الهيئة الوطنية للوقاية من الفساد ومكافحته - مجيدي, يحيي; عون, إسمهان (University of Eloued جامعة الوادي, 2019)
تحاول هذه الدراسة إبراز دور الهيئة الوطنية للوقاية من الفساد ومكافحته، وتقييم دورها وتحديد أهم العراقيل التي تعترض عملها بالإضافة إلى اقتراح الحلول والبدائل لتعزيز دور الهيئة في مكافحة ظاهرة الفساد. حيث تطرقنا في هذه المقالة إلى محورين أساسيين الأول يتطرق إلى استقلالية الهيئة الوطنية للوقاية من الفساد ومكافحته ، أما المحور الثاني يتطرق إلى محدودية دور الهيئة الوطنية للوقاية من الفساد ومكافحته. This study attempts to highlight the role of the National Commission for the Prevention and Control of Corruption, assess its role and identify the most important obstacles to its work, as well as propose solutions and alternatives to enhance the role of the Commission in combating corruption. In this article we discussed two main axes: the first deals with the independence of the National Commission for the Prevention and Combating of Corruption; the second focuses on the limited role of the National Commission for the Prevention and Control of Corruption.
مجلد3، عدد3
Keywords: الفساد – الهيئة الوطنية- الجزائر.; Corruption - National Authority - Algeria